Etika Bisnis Islami Dalam E-Commerce: Mengintegrasikan Teknologi Dan Nilai-Nilai Syariah - Hidayati, Qonita; Khairi, Rifqil (Journal of Economic, Management, Business, Accounting Sustainability, 2024)
This research aims to explore and analyze the application of Islamic business ethics in e-commerce with a focus on how technology can be integrated with sharia values. Using qualitative research methods with a descriptive-analytical approach, data was collected through in-depth interviews with Muslim e-commerce business people, sharia experts, and consumers, as well as direct observation and documentation analysis. The research results show that although there is a fairly good understanding of sharia principles such as honesty, justice and transparency, their implementation in e-commerce still faces various challenges. These challenges include a lack of in-depth understanding among business people, technological obstacles, and low consumer acceptance. However, this research also found that strategies such as education and training, development of sharia-supporting technology, and consumer awareness campaigns can overcome these challenges. Overall, the integration of technology with sharia values ​​in e-commerce not only enables businesses that comply with Islamic principles, but also opens up great opportunities for wider market development and increased consumer confidence. This research provides practical insights for Muslim business people and policy makers in implementing Islamic business ethics in the digital era.